An organoid model derived from human adipose stem/progenitor cells to study adipose tissue physiology. (31st December 2022) - Mandl, Markus; Viertler, Hans P.; Hatzmann, Florian M.; Brucker, Camille; Großmann, Sonja; Waldegger, Petra; Rauchenwald, Tina; Mattesich, Monika; Zwierzina, Marit; Pierer, Gerhard; Zwerschke, Werner
ABSTRACT: We established a functional adipose organoid model system for human adipose stem/progenitor cells (ASCs) isolated from white adipose tissue (WAT). ASCs were forced to self-aggregate by a hanging-drop technique. Afterwards, spheroids were transferred into agar-coated cell culture dishes to avoid plastic-adherence and dis-aggregation. Adipocyte differentiation was induced by an adipogenic hormone cocktail. Morphometric analysis revealed a significant increase in organoid size in the course of adipogenesis until d 18. Whole mount staining of organoids using specific lipophilic dyes showed large multi- and unilocular fat deposits in differentiated cells indicating highly efficient differentiation of ASCs into mature adipocytes. Moreover, we found a strong induction of the expression of key adipogenesis and adipocyte markers (CCAAT/enhancer-binding protein (C/EBP) β, peroxisome proliferator-activated receptor (PPAR) γ, fatty acid-binding protein 4 (FABP4), adiponectin) during adipose organoid formation. Secreted adiponectin was detected in the cell culture supernatant, underscoring the physiological relevance of mature adipocytes in the organoid model. Moreover, colony formation assays of collagenase-digested organoids revealed the maintenance of a significant fraction of ASCs within newly formed organoids. In conclusion, we provide a reliable and highly efficient WAT organoid model, which enables accurate analysis of cellular and molecular markers of adipogenic differentiation and adipocyte physiology.